Laju insiden gagal ASI eksklusif di masyarakat nelayan pada masa pandemi Covid-19 - Hari Santoso; Wiwit Estuti; M. Choiroel Anwar; Priyo Sulistiyono; Dewi Rahayu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Exclusive breastfeeding in Indonesia reached 37,3%. The Covid-19 pandemic has threatened to reduce exclusive breastfeeding coverage, which will impact the quality of human resources in the future. This study aims to determine the incidence rate of exclusive breastfeeding failure during the Covid-19 pandemic. Cohort study for nine months. In a fishing village, namely Dadap Village, Juntinyuat, Indramayu, West Java 2020. The population is all babies born during the study period, obtained 58 babies. Risk factor data were collected through interviews with questionnaires through home visits. Home visits were conducted six times during the observation period. The analysis was conducted by calculating the incidence rate using the formula for the number of cases of infants failing exclusive breastfeeding divided by the total number of live births during the observation period. The results showed that the incidence rate of exclusive breastfeeding failure in Dadap Village was 96,6 per 100 live births. Complementary feeding was given in formula milk in the first week (84,5%), even 79,3% of it after birth. Mothers and husbands do not know about exclusive breastfeeding (75,9%). The mother took the initiative to provide early complementary feeding with the support of her husband (63,8%). Mothers experience problems in breastfeeding (87,9%), and mothers cannot cope with the problem. In conclusion, the causes of exclusive breastfeeding failure in fishing villages are low income, low maternal education and knowledge, and lack of husband support.